2022
DOI: 10.7759/cureus.24856
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Structure, Synthesis, and Its Applications: A Systematic Review

Abstract: Resorbable collagen has been utilized to treat wounds, close graft, and tooth extraction sites, and enhance recovery. Collagen-based membranes are also used as barriers in periodontal and implant therapy to limit epithelial migration and allow cells with the regenerative capacity to fill the problem area. This systematic review was carried out to analyze the studies focusing on collagen structure, synthesis, and its applications. A detailed and extensive search was performed with the help of the keywords "coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Whereas scientific community in the 1970s talked about only four types of genetically distinct collagens [ 23 ], at present it is generally accepted that collagen superfamily comprises up to 28 members that differ from each other in molecular composition as well as in their supramolecular organization within the ECM [ 24 , 25 , 26 , 27 ]. The occurrence of an additional collagen type, called collagen XXIX, has been also claimed by some authors [ 28 , 29 ], although, given that COL29A1 gene was shown to be identical to the COL6A5 gene and that the a1(XXIX) chain corresponds to the a5(VI) [ 30 ], collagen XXIX is not generally accepted as a genetically distinct family [ 24 ].…”
Section: Understanding Collagen Worldmentioning
confidence: 99%
“…Whereas scientific community in the 1970s talked about only four types of genetically distinct collagens [ 23 ], at present it is generally accepted that collagen superfamily comprises up to 28 members that differ from each other in molecular composition as well as in their supramolecular organization within the ECM [ 24 , 25 , 26 , 27 ]. The occurrence of an additional collagen type, called collagen XXIX, has been also claimed by some authors [ 28 , 29 ], although, given that COL29A1 gene was shown to be identical to the COL6A5 gene and that the a1(XXIX) chain corresponds to the a5(VI) [ 30 ], collagen XXIX is not generally accepted as a genetically distinct family [ 24 ].…”
Section: Understanding Collagen Worldmentioning
confidence: 99%
“…The structure of the collagen molecule can also influence its biosynthesis. 3,125 For example, collagen biosynthesis is affected by the ratio of the triple helix to α-helix structure, the molecular weight and the amino acid sequence of the collagen. The triple helical structure of the type I collagen heterotrimer may protect the molecule to some extent from enzymatic breakdown.…”
Section: Collagen Molecular Structure and Molecular Weightmentioning
confidence: 99%
“…The collagen peptide scaffold is a medical scaffold that utilizes the biocompatibility, biodegradability, and biological activity of collagen peptides as a material for tissue engineering and regenerative medicine. 3 Using scaffolds to aid in tissue regrowth and repair allows for the treatment of various tissue defects. In the medical field, collagen peptide scaffolds have been used to repair and regenerate bone, cartilage, dental, cardiovascular, and neural tissues.…”
Section: Medical Devices and Medicinesmentioning
confidence: 99%
See 2 more Smart Citations